Budidaya Selada secara Hidroponik di Balai Pengkajian Teknologi Pertanian Jalan Mentok, Kepulauan Bangka Belitung - Sulaiman, Firdaus; Anggito Aritonang, Alfredo Grace; Habibah, Dhia Fauzia; Yemima Sitompul, Grace Enita; Trijayanti, Selfy; Yuniarti, Yuniarti; Rizky Sitorus, Victoria Junyta (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Sulaiman, F., Aritonang, A. G. A., Habibah. D.F., Sitompul, G. E. Y., Trijayanti., S., Yuniarti, Y., Sitorus, V.J.R. (2023). Hydroponic lettuce cultivation at the agricultural technology assessment Center Jalan Mentok, Bangka Belitung Islands. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 230-236). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Lettuce is an agricultural product that is generally consumed in fresh form to produce good hygiene. For the benefit of human beings, which is a top priority, as the population of Indonesia increases, market demand in the food sector will also increase. The aimed of this research is to give the students work experience and knowledge in the field of hydroponics. The methods used in this study were observational and participatory. Results of this study were obtained when the 2nd DAP (Day After Plantation) carried out a nutritional solution check. Since the salad is already quite large and the nutrients are reduced, first nutritional addition was made to 425 ppm with Ph 6.1. Second nutritional component was added at 14 DAP to 570 ppm at pH 6.4.Third nutritional addition at 24 DAP was 745 ppm at pH 6.7. Fourth nutritional addition at 31 HST until the harvest was 800 ppm at pH 6.8. The nutrient solution is an important factor in this study because it is a determinant of the success of hydroponic cultivation. A nutrient requirement that is effectively met for the celery can make its growth more optimal. Generally speaking, hydroponics requires essential nutrients consisting of macro and micronutrients. The advice that can be given is need to increase the sustainability of hydroponic crop cultivation activities in the greenhouse as well as improve development on the basis of IoT (the Internet of Things) for automatic nutrition systems so that the quality of the plants produced is even better.